Chronic exposure to inhaled vaporized cannabis high in Δ9-THC alters brain structure in adult female mice - Taylor, Autumn; Nweke, Amanda; Vincent, Veniesha; Oke, Marvellous; Kulkarni, Praveen; Ferris, Craig F. (Frontiers in Neuroscience, 2023)
The medical and recreational use of cannabis has increased in the United States. Its chronic use can have detrimental effects on the neurobiology of the brain – effects that are age-dependent. This was an exploratory study looking at the effects of chronically inhaled vaporized cannabis on brain structure in adult female mice. Adult mice were exposed daily to vaporized cannabis (10.3% THC and 0.05% CBD) or placebo for 21 days. Following cessation of treatment mice were examined for changes in brain structure using magnetic resonance imaging. Data from voxel-based morphometry and diffusion weighted imaging were registered to, and analyzed with, a 3D mouse MRI atlas with 139 brain areas. Mice showed volumetric changes in the forebrain particularly the prefrontal cortex, accumbens, ventral pallidum and limbic cortex. Many of these same brain areas showed changes in water diffusivity suggesting alterations in gray matter microarchitecture. These data are consistent with much of the clinical findings on cannabis use disorder. The sensitivity of the dopaminergic system to the daily exposure of vaporized cannabis raises concerns for abuse liability in drug naïve adult females that initiate chronic cannabis use.